Paediatric Free Open Access Meducation (FOAM): behaviours, trends and implications. Issue 1135 (10th February 2020) - Barton, Jack; Round, Jonathan; Knight, Katie
Abstract: Introduction: Free Open Access Meducation (FOAM) describes online resources assisting learning in medicine. Little is known about users or their behaviours. Methods: Using Google Analytics for a popular FOAM site (www.paedatricfoam.com ), we explored user demographics and patterns of behaviour. We analysed these further with descriptive and statistical tests using SPSS (version 26). Data are presented as mean (SD). Results: There were 181.44 (75.16) mean daily users accessing the site throughout a 4-month period during 2018/2019. 68.9% of users were female; 44% were 25–34 years; 57.3% used a mobile device. The mean session duration was 73.55 (9.41) seconds, with more time spent per session and a greater number of pages per session observed in users accessing the site from a desktop or tablet as opposed to a mobile phone. 84.3% of mobile users left the site after viewing a single page. Referral source was also associated with device used (p<0.001). Age was not related to user behaviours (p>0.05). Discussion: FOAM is a rapidly developing form of medical education, with large user numbers seen for a site just 2 years old. The site is being used by many beyond its intended readership. Rather than accessing multiple pages from a desktop, users have varied online behaviours, with the majority viewing a single page on a mobile phone, referred by social media or Google. Conclusions: Google Analytics can powerfully display usage of medical websites but has important limitations if statistical exploration is required. FOAM users are a heterogenous group, and thus content should be designed with this in mind. Further research must be prioritised focussing on the scope, curriculum coverage, accuracy of information and the effectiveness of FOAM as an educational resource.